Prevalence of smoking habits, attitudes, knowledge and beliefs among Health Professional School students: a cross-sectional study - Margherita Ferrante; Rosella Saulle; Caterina Ledda; Roberto Pappalardo; Roberto Fallico; Giuseppe La Torre; Maria Fiore (Istituto Superiore di Sanità, 2013)
OBJECTIVES: To examine smoking prevalence, attitudes, knowledge and behaviours/beliefs among Health Professional School students according to the Global Health Professional Student Survey (GHPSS) approach. METHODS: A cross-sectional study was carried out in Catania University Medical Schools. The GHPSS questionnaires were self-administered. Logistic regression model was performed. The level of significance was p < 0.05. RESULTS: 422 students answered to the questionnaire. Prevalence of current smokers was 38.2%. 94.3% of the total sample believe that health professionals should receive specific training to quit smoking, but only 21.3% of the sample received it during the study courses. CONCLUSIONS: Given the high prevalence of smokers among health professionals and their key role both as advisers and behavioral models, our results highlight the importance of focusing attention on smoking cessation training addressed to them.